Effects of amyloid precursor protein peptide APP96-110, alone or with human mesenchymal stromal cells, on recovery after spinal cord injury - Stuart I Hodgetts; Sarah J Lovett; D Baron-Heeris; A Fogliani; Marian Sturm; C Van den Heuvel; Alan R Harvey (Neural Regeneration Research, 2022)
Delivery of a peptide (APP96-110), derived from amyloid precursor protein (APP), has been shown to elicit neuroprotective effects following cerebral stroke and traumatic brain injury. In this study, the effect of APP96-110 or a mutant version of this peptide (mAPP96-110) was assessed following moderate (200 kdyn, (2 N)) thoracic contusive spinal cord injury (SCI) in adult Nude rats. Animals received a single tail vein injection of APP96-110 or mAPP96-110 at 30 minutes post-SCI and were then assessed for functional improvements over the next 8 weeks. A cohort of animals also received transplants of either viable or non-viable human mesenchymal stromal cells (hMSCs) into the SC lesion site at one week post-injury to assess the effect of combining intravenous APP96-110 delivery with hMSC treatment. Rats were perfused 8 weeks post-SCI and longitudinal sections of spinal cord analyzed for a number of factors including hMSC viability, cyst size, axonal regrowth, glial reactivity and macrophage activation. Analysis of sensorimotor function revealed occasional significant differences between groups using Ladderwalk or Ratwalk tests, however there were no consistent improvements in functional outcome after any of the treatments. mAPP96-110 alone, and APP96-110 in combination with both viable and non-viable hMSCs significantly reduced cyst size compared to SCI alone. Combined treatments with donor hMSCs also significantly increased βIII tubulin+, glial fibrillary acidic protein (GFAP+) and laminin+ expression, and decreased ED1+ expression in tissues. This preliminary study demonstrates that intravenous delivery of APP96-110 peptide has selective, modest neuroprotective effects following SCI, which may be enhanced when combined with hMSC transplantation. However, the effects are less pronounced and less consistent compared to the protective morphological and cognitive impact that this same peptide has on neuronal survival and behaviour after stroke and traumatic brain injury. Thus while the efficacy of a particular therapeutic approach in one CNS injury model may provide justification for its use in other neurotrauma models, similar outcomes may not necessarily occur and more targeted approaches suited to location and severity are required. All animal experiments were approved by The University of Western Australia Animal Ethics Committee (RA3/100/1460) on April 12, 2016.